Strategi Penyampaian Pesan Dakwah Jama’ah Tabligh di Lingkungan Masjid Sumber Bungur Kecamatan Pakong Kabupaten Pamekasan - Ahmad Noval Romsi (Jurnal Al-Tatwir, 2021)
Some of today's Muslims often limit their perception of their religion as a physical identity. However the so-called identity itself has already deteriorated, only leaving their Islamic identity shown in the form of a single sheet of identity card. Such phenomenon is what causes the term "Islam KTP" (Islam ID card) to emerge. The way to strengthen and unify the Islamic society, as a basis of strength to fight the propagandas of the infidels that can poison the creed of the Muslims, is through the da'wah movement. The Tablighi Jamaat attempts to carry out a da'wah method that is in accordance with the da'wah method of Rasulullah SAW, which is called the nubuwah da'wah method. The current study has two focuses: First, how the Da'wah strategy of the Tablighi Jamaat in Masjid Sumber Bungur was carried out; Second, the contents of the da'wah message conveyed by the Tablighi Jamaat in Masjid Sumber Bungur. This study employs a descriptive qualitative approach. The data were obtained through interviews, observations and documentation. Meanwhile, the informants were the Jamaat Leader (Expert in Suro), Ustad Khafifi, Mr. Ahmad, and Mr. Wahab as the members of the Jamaat, and Mr. Pudin, Mr. Abdul Hasan, and Mr. Saleh (from the community who have been visited by the Jamaat). The data validation was done through the extension of participation, persistence of observation, and triangulation. The results of the study related to the da'wah strategy are namely: a) Tablighi Jamaat's da'wah strategy in terms of planning, they had a consensus on the programs to be implemented. b) Tablighi Jamaat's strategy in terms of implementation is to have further actions towards a program that has been given a prior consensus c) Tablighi Jamaat's da'wah strategy in terms of evaluation is divided into two forms: the external and internal evaluations. The results of the study related to the contents of da'wah are namely: a) an unstructured organization b) a rather conservative type of preaching, which means it does not adapt to the current conditions. c) Da'wah is delivered in translation without mentioning the matan of the hadith.